Harry C. Hale, Digest of the City of Little Rock, Arkansas, Embracing the Ordinances and Resolutions of a General Character Passed by the City Council of Said City Up to and Including the Session of September 21, 1914, at 97, § 463 (1915) - (:unkn) unknown (My University, 1869)
Prohibited the discharge of any cannon, gun, fowling piece, pistol, or fire-arms of any description. Violators fined not less than two but no more than ten dollars.
Keywords: DISCHARGE